Biotransformation of gluten-free composite flour mediated by probiotics via solid-state fermentation process conducted under different moisture contents - Koyum, Kareem Adebayo; Foo, Hooi Ling; Ramli, Norhayati; Loh, Teck Chwen (Frontiers in Nutrition, 2023)
Staple foods produced from composite flour are considered feasible to alleviate protein-energy malnutrition (PEM). However, one of the major limitations of composite flour is poor protein digestibility. The biotransformation process mediated by probiotics via solid-state fermentation (SSF) holds a promising potential to address the poor protein digestibility in composite flour. Yet, there is no report established in this regard to the best of our knowledge. Therefore, 4 strains of Lactiplantibacillus plantarum and Pediococcus pentosaceus UP2 isolated from Malaysian foods that were previously reported to produce versatile extracellular hydrolytic enzymes were employed to biotransform gluten-free composite flour derived from rice, sorghum, and soybean. The SSF process was performed under 30–60% (v/w) moisture content for 7 days, where samples were withdrawn at 24 h intervals for various analyses such as pH, total titratable acidity (TTA), extracellular protease activity, soluble protein concentration, crude protein content, and in vitro protein digestibility. The pH of the biotransformed composite flour showed a significant reduction from the initial range of pH 5.98–6.67 to the final pH of 4.36–3.65, corresponding to the increase in the percentage of TTA in the range of 0.28–0.47% to 1.07–1.65% from days 0 to 4 and remained stable till day 7 of the SSF process. The probiotics strains exhibited high extracellular proteolytic activity (0.63–1.35 U/mg to 4.21–5.13 U/mg) from days 0 to 7. In addition, the treated composite flour soluble protein increased significantly (p ≤ 0.05) (0.58–0.60 mg/mL to 0.72–0.79 mg/mL) from days 0 to 7, crude protein content (12.00–12.18% to 13.04–14.39%) and protein digestibility (70.05–70.72% to 78.46–79.95%) from days 0 to 4 of SSF. The results of biotransformation of 50% (v/w) moisture content were mostly comparable to 60% (v/w) moisture content, implying 50% (v/w) moisture content was the most suitable moisture content for the effective biotransformation of gluten-free composite flour mediated by probiotics via SSF since flour quality is better at lower moisture content. As for the overall performance, L. plantarum RS5 was ranked the best strain, attributed to the general improvement in the physicochemical properties of composite flour.